НОВЫЕ ВОЗМОЖНОСТИ ДИАГНОСТИКИ ХРОНИЧЕСКОЙ СЕРДЕЧНОЙ НЕДОСТАТОЧНОСТИ У ПАЦИЕНТОВ С САХАРНЫМ ДИАБЕТОМ 2 ТИПА - А. А. Снеткова; Н. Ю. Тимофеева; Т. В. Адашева (Архивъ внутренней медицины)
The aim of the study was to examine the plasma concentrations of galectin-3 and brain natriuretic peptide (BNP), indicators of antioxidant protection, oxidative stress, systemic inflammation and endothelial dysfunction, central hemodynamic parameters.Materials and Methods: The study included patients with CHF without metabolic disturbances (n = 30) and with the combination of heart failure and diabetes mellitus (DM) type 2 (n = 60). Results: Patients with chronic heart failure, having as co-morbidity of DM have higher levels of biomarkers of heart failure (galectin-3 (R≤0,001), BNP (R≤0,001), as well as more significant changes in hemodynamic parameters. In the group of patients with CHF with preserved ejection fraction (EF) revealed higher levels of galectin-3 (0.955 [0.886; 1,010] ng / ml) compared to patients with reduced ejection fraction (0.816 [0.776; 0.934] ng / ml) (P = 0,01). The level of galectin-3 above 1ng / ml is associated with a poor prognosis for the frequency of hospitalizations in patients with CHF.